Calix[4]pyrrole hydridosilicate: the elusive planar tetracoordinate silicon imparts striking stability to Its anionic silicon hydride - Ebner, Fabian; Greb, Lutz (Journal of the American Chemical Society, 2018)
Anionic hydridosilicates are highly reactive and strong hydride donors. In contrast, calix[4]pyrrole hydridosilicate is an entirely water-stable, anionic silicon hydride, which does not show hydridic reactivity. However, it still acts as an electron donor and enables the detection of a single electron transfer process in the reduction chemistry with hydridosilicates. Most important, these unusual properties are imparted by the unique planar structure of its elusive parent neutral silane-substantiating the effect of planar tetracoordinate silicon for the first time.